2021
DOI: 10.1155/2021/8827891
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Pretreatment Regulates Apoptosis of Myocardial Ischemia-Reperfusion Injury in Rats Through RhoA/p38MAPK Pathway Mediated by miR-133a-5p

Abstract: The electroacupuncture (EA) pretreatment possesses a beneficial effect on myocardial ischemia/reperfusion (I/R) injury. However, the molecular mechanism of the EA effect is not fully understood. The study aimed to explore the protective effect of EA pretreatment on myocardial ischemia-reperfusion injury (MIRI) and apoptosis-related mechanisms in rats. Rats underwent in vivo myocardial ischemia-reperfusion, EA pretreatment, or intravenous injection of antagomirs. Cardiac function, infarct area, and myocardial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…e pathophysiological mechanism of myocardial ischemia-reperfusion injury is complex. Studies have shown that myocardial ischemia can promote in ammation and oxidative stress translation and can lead to myocardial apoptosis through reperfusion, in which inammatory factors can activate and chemotaxis leukocytes, which are also the products of activation of the leukocytes, which can aggravate myocardial injury [1,[7][8][9]. Superoxide dismutase (SOD) is essential to prevent oxidative stress, and it can e ectively resist the damage of oxygen free radicals to the body through its antioxidant and antifree radical functions [10].…”
Section: Introductionmentioning
confidence: 99%
“…e pathophysiological mechanism of myocardial ischemia-reperfusion injury is complex. Studies have shown that myocardial ischemia can promote in ammation and oxidative stress translation and can lead to myocardial apoptosis through reperfusion, in which inammatory factors can activate and chemotaxis leukocytes, which are also the products of activation of the leukocytes, which can aggravate myocardial injury [1,[7][8][9]. Superoxide dismutase (SOD) is essential to prevent oxidative stress, and it can e ectively resist the damage of oxygen free radicals to the body through its antioxidant and antifree radical functions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a previous study reported that EA at Zusanli acupoint (ST36) can induce protective effects on myocardial injury in a rat model of sepsis by reducing myocardial NO level (Zhang et al, 2018). Other researchers found that EA pretreatment at Neiguan (PC6) acupoint can alleviate myocardial ischemia–reperfusion injury in rats with lower iNOS levels in the serum (Han et al, 2021). Another study suggested that EA at PC6 acupoint could prevent Doxorubicin‐induced cardiotoxicity through reducing NO production by decreasing the expression of iNOS in myocardial tissue of a mouse model (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…MIRI is common in patients with cardiovascular disease and in patients undergoing cardiopulmonary bypass and heart surgery [31]. Currently, pretreatment is often used in the treatment of MIRI and involves short-term non-destructive stimulation before injury onset in order to improve the tolerance of tissues or organs to subsequent permanent and fatal injury, and is considered one of the most effective mechanisms of endogenous protection [32]. EA pretreatment can attenuate MIRI and improve the quality of life of patients [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%